Indian painting: the lesser-known traditions - Dallapiccola, Anna Libera 1944- (Niyogi Books, 2011)
Papers presented at a conference on Indian painting : the lesser-known traditions, held in Houston during 8-9 March 2008
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Konferenzschrift; Miniatur; Malerei; Indien